The Effective Approaches in Instilling and Developing Early Childhood Social-Emotional Aspects at TK Negeri Pembina Sitiung - Salahuddin, Amar; Sari, Fitria; Agustiyan, Dimas (The Future of Education Journal, 2025)
Social emotional problems in early childhood can hinder the learning process and social development. This study aims to analyze the approaches used by teachers in instilling and developing the social emotional aspects of early childhood in Pembina Sitiung State Kindergarten, and to find out the most effective approach. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers use play, role model, and habituation approaches in instilling social emotional values. The collaborative play approach and adult role models have proven to be the most effective in shaping positive social behavior in children. This study recommends the importance of ongoing teacher training related to approaches that are oriented towards strengthening children's social emotional values.